HUBUNGAN ANTARA KECERDASAN EMOSIONAL DENGAN KEMATANGAN KARIR PADA SISWA KELAS XI SMK NEGERI 2 DEMAK - MUSTIKANINGRUM, LENA; Desiningrum, Dinie Ratri (Empati, 2017)
Career maturity is a situation where a person is able to complete the task of typical career development in accordance with the stage of development and chronological age. This study aims to determine the relationship between emotional intelligence with career maturity in XI grade SMK Negeri 2 Demak. The population of this study is all students of XI grade SMK Negeri 2 Demak. Population amounted to 357 people, and the study sample amounted to 178 people. The sampling technique was done by cluster random sampling technique. Measuring tool uses career maturity scale (30 aitem, Î± = 0,883) and emotional intelligence scale (29 aitem, Î± = 0,872). Data analysis technique in this research is simple regression analysis. This research shows rxy = 0,230; Î¡ = 0.002 (Ï <0.05). The results of data analysis explain that there is a positive and significant relationship between emotional intelligence with career maturity. The higher emotional intelligence then the higher career maturity. Otherwise , the lower emotional intelligence then the lower career maturity. The effective contribution of emotional intelligence to career maturity is 5.3% and 94.7% is influenced by other factors not revealed in this study.Â Â